Dynamic connectedness between cryptocurrencies and currencies: Analyzing the impact of CHF and JPY on bitcoin and Ethereum - Belkhir, Nadia; AOUN, Olfa EL (International Journal of Innovative Research and Scientific Studies, 2025)
This study provides a comprehensive analysis of the dynamic interconnectedness between traditional fiat currencies (CHF and JPY) and cryptocurrencies (Bitcoin and Ethereum) across three distinct periods: the pre-COVID-19, the COVID-19 pandemic, and the Russia-Ukraine conflict. Our methodology employs the Quantile Vector Autoregressive (QVAR) connectivity approach, beginning with the average median and progressively extending to various quantiles over time revealing both short-term and long-term dynamic connectedness. Our findings reveal that Bitcoin and Ethereum exhibit significant interconnectedness and predominantly act as net transmitters of volatility, especially in the short term. In contrast, CHF and JPY generally serve as shock absorbers, showing strong self-dependency and conditional safe-haven properties. Particularly, the Swiss Franc occasionally transmits volatility during extreme market conditions, highlighting its dynamic role. The implications of our study are crucial for investors and portfolio managers aiming to adjust dynamically their portfolios by actively monitoring market trends to modify their allocations between traditional safe-haven currencies and cryptocurrencies. Specifically, in times of increased volatility, managers should temporarily reduce exposure to cryptocurrencies and increase allocations in stable fiat currencies such as CHF and JPY. Conversely, during more stable periods, higher investments in cryptocurrencies could yield better returns. implementing a real-time volatility monitoring system can aid managers in making well-informed choices to optimize risk management strategies. Dynamic hedging is preferred over static approaches.